1985
DOI: 10.1128/jvi.55.3.886-889.1985
|View full text |Cite
|
Sign up to set email alerts
|

trans-Activation of parvovirus P38 promoter by the 76K noncapsid protein

Abstract: The autonomously replicating parvoviruses contain a 5-kilobase linear single-stranded DNA genome that produces two noncapsid proteins, Ni and N2, and two overlapping capsid proteins, VP1 and VP2. To characterize the regulation of viral transcription, we began with a study of the promoter for the coat proteins (P38) at map unit 38. Various constructions containing the P38 promoter were fused to the bacterial gene for chloramphenicol acetyltransferase (cat), and the relative efficiency of expression was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
95
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 33 publications
6
95
0
Order By: Relevance
“…The most striking observation from the in vivo experiments was that deletion of a 46-bp fragment (-167 to -121, nt 1838 to 1884) containing the 30-bp TAR motif resulted in a threeto eightfold increase in transcription over the wild-type promoter. Given the reports on trans activation of P38 by the viral NS proteins in both H-1 virus (21,24) and MVM(i) (10), these data suggested that trans activation might be due to the relief of repression rather than to positive regulation. Furthermore, the proximity of the TAR element to the CCAAT box and the demonstrated functionality of the CCAAT motif in the fully active (derepressed) promoter in vivo, suggest that repression at P38 may be mediated through this sequence.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The most striking observation from the in vivo experiments was that deletion of a 46-bp fragment (-167 to -121, nt 1838 to 1884) containing the 30-bp TAR motif resulted in a threeto eightfold increase in transcription over the wild-type promoter. Given the reports on trans activation of P38 by the viral NS proteins in both H-1 virus (21,24) and MVM(i) (10), these data suggested that trans activation might be due to the relief of repression rather than to positive regulation. Furthermore, the proximity of the TAR element to the CCAAT box and the demonstrated functionality of the CCAAT motif in the fully active (derepressed) promoter in vivo, suggest that repression at P38 may be mediated through this sequence.…”
Section: Discussionmentioning
confidence: 72%
“…Although the majority of the viral message (65 to 70%) in a productive infection is transcribed from the P38 promoter, the cloned P38 promoter has proven to be relatively weak both in vivo and in vitro, while the cloned P4 promoter is quite strong (1). This apparent paradox has been resolved by recent findings which demonstrate that the NS proteins of the autonomous parvoviruses activate the P38 promoter in trans, apparently by increasing the rate of transcription (10,21,24). This type of genomic organization suggested a classic early-to-late switch in viral gene expression; however, evidence that the appearance of viral mRNA coding for the NS proteins precedes viral capsid mRNAs has only recently been presented (8).…”
mentioning
confidence: 99%
“…The growth medium was replaced with MEM containing 10% dialyzed serum 12 h before the addition of 20 ,uCi of [35S]methionine (1,000 Ci/mmol; New England Nuclear Corp., Boston, Mass.) per ml, and lysates were prepared 24 h after the addition of the isotope. The serum used as the first antibody was anticapsid antibody (rabbit 0118) or serum from a calf experimentally infected and immunized with BPV (calf 86).…”
Section: Methodsmentioning
confidence: 99%
“…According to recent studies one or more of the nonstructural proteins of AAV are involved in trans-regulation of AAV gene expression [24,25]. Finally, Rhode [26] has shown that the P38 promoter of the parvovirus H-1 is transactivated by the NS-1 protein.…”
Section: Structure and Organization Of The Genomementioning
confidence: 99%